Photodynamic Diagnosis for the Identification of Intestinal-Type Gastric Cancers and High-Grade Adenomas - Kurumi, Hiroki; Sakaguchi, Takuki; Hashiguchi, Keiichi; Yamashita, Taro; Fujii, Masashi; Ikebuchi, Yuichiro; Yoshida, Akira; Isomoto, Hajime (Frontiers in Oncology, 2022)
Gastric cancer is the second most common cancer in Japan. The incidence of gastric cancer remains high owing to the increase in the elderly population. Endoscopy outperforms radiography for identifying early gastric cancer (EGC). Furthermore, image-enhanced endoscopy (IEE) has been developed and implemented worldwide in clinical practice. Magnifying IEE images can help to visualize the microvascular pattern and microstructure architecture, which is used for the characterization of EGC. However, accurate endoscopic diagnosis requires the experience and skill of endoscopists, making an objective and simple diagnostic method desirable. In this retrospective study, we investigated the diagnostic yield of 5-aminolevulinic amino acid (5-ALA)-mediated photodynamic diagnosis (PDD) for identifying gastric cancers and high-grade adenomas. In total, 52 lesions from 43 patients were ultimately included in the study. We detected 5-ALA-mediated protoporphyrin IX fluorescence in 45 of the 52 lesions that were initially intended for PDD, resulting in a detection rate of 86.5%. Whereas three signet ring cell carcinoma lesions were negative using 5-ALA PDD, all high-grade adenomas were identified. In eight of the patients with multiple lesions, 17 lesions were identified using 5-ALA PDD. Again, we took biopsies from six areas which we suspicious as new lesions. The three lesions were adenocarcinoma, one lesion was adenoma, and another two lesions were normal. Preoperative 5-ALA-PDD could provide additional diagnostic yields to detect such multiple lesions, including high-grade adenomas, simultaneously. No severe adverse events were observed. Prospective multicenter studies are warranted to confirm the usefulness of 5-ALA PDD for EGC identification.